Framework for enhancing Students’ Smartphone Learning Ability: A Case Study of Nigerian Public Universities - Godswill Ejeohiolei, Esechie; Chukwuka Christian, Ohueri; Siti Zanariah, Ahmad Ishak; Peter Karubi, Nwanesi (Emerald Publishing, 2022)
Purpose – The importance of smartphones in enhancing students learning, research and development is well-established in many published studies. Nevertheless, due to numerous challenges, Nigerian students are yet to reap from the benefits of smartphones in terms of accessing vital information for learning and development. Therefore, this study aims to develop a framework that will enhance Nigerian students’ ability to use smartphones for learning. Design/methodology/approach – The SERVQUAL Theory Framework is adapted to actualize the research aim. Moreover, a qualitative (in-depth interview) re students from 3 public universities in Nigeria. Purposive sampling technique was used to select the interviewees, and the interview data were analysed using thematic content analysis. Findings – The findings identified the critical constraints that deter Nigerian students from reaping the full potential of smartphones for learning. The constraints are categorized into three groups which include telecommunication companies’ hiccups, such as high cost of internet, poor network services and coverage; government obstacles, such as high tax policies, insufficient electricity supply and lack of basic infrastructure; and university barriers, such as unavailability of Wi-Fi connection for students, lack of equipped university libraries and poor management. Originality/value – Thus, a holistic Framework for Enhancing Students Smartphones Learning Ability was established to provide fundamental recommendations to the Nigerian Government, telecommunication companies in Nigeria and Nigerian universities to tackle the pressing issues hindering Nigerian students from using their smartphones for learning. This will enhance the smartphone learning experience of Nigerian students.